Optimation Transesterification Reaction Conditions on Biodiesel Production From Beef Tallow - Rosmawaty, Rosmawaty; Bandjar, Adriani; Gunoroso, Suntoro (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2015)
Biodiesel synthesis has been done from beef tallow through two step, esterification and transesterification reactions. Esterification process is done by using H2SO4 1M as a catalyst, methanol 1:9, temperature of 60-65°C, and for 3 hours. After separated between methanol and trigyceride, then proceed to the process of transesterification. To obtain the optimum reaction conditions then used some transesterification process variables, there are: the weight percentage catalyst of KOH between 0.1, 0.5, 1; 1.5, and 2%, the reaction time of 1-5 hours and the reaction temperature between 50 -70 oC. Optimum conditions of transesterification reaction for the synthesis of biodiesel derived from beef tallow with KOH catalyst is as follows: the weight percentage of 1% KOH catalyst, the reaction time of 3 hours and the reaction temperature of 65 oC. The results of physical testing of biodiesel fuel by ASTM method includes specific density of 0.8675 g/cm3, kinematic viscosity of 4.971 mm2/s, flash point of 134.5°C, pour point of 27°C, the Conradson carbon residue of 0.018%, and the copper corrosion-pieces of 1B.